PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL INTERAKTIF PENDEKATAN CTL PEMBELAJARAN TEMATIK TERPADU TERHADAP HASIL BELAJAR SISWA KELAS VI SEKOLAH DASAR - Mega Rosa S Purba; Regina Fredika Sipayung (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2024)
This study aims to prove the effect of interactive audio-visual media with a CTL approach to student learning outcomes in integrated thematic learning in grade VI SD with the research methodology used is quasi-experimental research, the sample in this study is grade VI students of SD Kartini Medan. Data collection techniques using tests. Hypothesis testing in this study is to use the t-test formula. The results of the study based on the calculation of the t-test on the posttest obtained tcount (2.7689) > ttable (1.9977) which means H0 is rejected and H1 is accepted. So it can be concluded that there is a positive effect of interactive audio visual media using the CTL approach on student learning outcomes in integrated thematic learning in class VI SD Kartini Medan.